Rhetoric and food. Semantic relationships and interconnections - Prato, Alessandro (E|C, 2020)
The paper investigates the relationship between food and language, especially its methaporic dimension. The symbolic functions of food can be traced in the verbal language through the use of metaphors or metonymies based on the relationships between food and other semantic fields such us knowledge or religion. Rhetoric uses terms related to food in establish a literary metalanguage that is still in use in the discipline.